Risk Analysis of Severe Thrombocytopenia in Nasopharyngeal Carcinoma During Concurrent Radio-Chemotherapy - Hu, Jialing; Tang, Luoyong; Cheng, Yunqi; Liu, Anwen; Huang, Long (Frontiers in Oncology, 2022)
Abstract Objective: To explore the risk factors and predictive indexes of severe thrombocytopenia during concurrent radio-chemotherapy of nasopharyngeal carcinomas Methods: Retrospective analysis were performed from the hospitalized patients with nasopharyngeal carcinoma from August 2014 to July 2017 and completed induction chemotherapy and concurrent radio-chemotherapy. According to the lowest platelet count during concurrent chemotherapy, patients were divided into observation and control group. The general information and laboratory examinations were recorded and analyzed by univariate analysis, multivariate regression analysis and ROC curve analysis. Results: Take the factors, including Age, PLT, IBIL, APTT at first visit, WBC, RBC, HGB, PLT, NEUT, APTT,IBIL, FFA, Crea、Urea before radio-chemotherapy, which are significant in univariate analysis into multivariate regression analysis. It turned out that RBC（OR=10.060, 95%CI2.679-37.777, P=0.001）,PLT(OR= 1.020, 95%CI1.006-1.034, P=0.005) and IBIL（OR=0.710,95%CI 0.561-0.898, P= 0.004） are independent predictors of severe TP in NPC. ROC analysis showed that the AUC of RBC, IBIL, PLT, AGE is 0.746(P< 0.001), 0.735（P<0.001）, 0.702(P=0.001), 0.734（P<0.001）. New variables called joint predictor was calculated by regression equation (Y=2.309*RBC-0.343*IBIL+0.02*PLT-10.007), the AUC of which is 0.870（P<0.001）, best truncation value is＞5.87 mmol/L. Conclusions: Lower RBC, PLT, higher IBIL before concurrent radio-chemotherapy are the independent risk factors causing severe TP during concurrent radio-chemotherapy of NPC. The RBC, PLT, IBIL before concurrent radio-chemotherapy and joint predictor have a good predictive value to evaluate the risk of severe TP during concurrent radio-chemotherapy of NPC.